Cloud Computing Characteristics and Services: A Brief Review - Rashid, Aaqib; Chaturvedi, Amit (International Journal of Computer Sciences and Engineering, 2019)
This study helps organizations and individuals understand how cloud computing can provide them with reliable, customized and cost-effective services in a wide variety of applications. In this paper, we have tried to explore various cloud computing services, applications and characteristics; we give various examples for cloud services delivered by the most common Cloud Service Providers (CSPs) such as Google, Microsoft, and Amazon. We have also discussed cloud computing service models and their benefits.